Nach der Zeitenwende: weniger Russland im deutschen Aussenhandel? - Schrader, Klaus (Estonian Discussions on Economic Policy, 2024)
The Russian war of aggression against Ukraine on February 24, 2022, prompted the German government to fundamentally rethink Germany's political and economic relations with Russia. A “change of times” was proclaimed which meant a caesura in foreign and security policy as well as the overcoming of economic dependencies on Russia. This article analyzes whether Germany has substantially reduced its foreign trade relations with Russia more than a year after this proclamation. It is shown that on the German export side, there was no substantial dependence on exports to Russia in any significant sector in the year of war 2022. The loss of importance of trade with Russia had no negative impact on the overall development of German exports. However, the momentum of Russian exports was already broken after the occupation of Crimea in 2014. On the import side, in contrast, a substantial reduction in trade relations did not take place before. Until 2022, dependencies on Russia as a supplier of raw materials remained high, especially in the case of pipeline-bound natural gas with a Russian import share of 55 percent. Germany corrected this political error at high cost and made itself independent of Russian natural gas imports by the end of 2022